Determining the relationship between body mass index, healthy lifestyle behaviors and social appearance anxiety - SABUNCULAR, GÜLEREN (TAYLOR & FRANCIS INC, 2018)
The aim of this study was to describe the relationship between nutritional status, healthy lifestyle behaviors and social appearance anxiety of individuals aged 20-65 (n=500). A significant, positive relationship was seen between body mass index and nutrition, and negative relationship between body mass index and spiritual development, interpersonal relations, stress management. There was a negative relationship between the ORTO-15 score and health responsibility, physical activity, nutrition, spiritual development, interpersonal relationships, stress management. There was also a negative relationship between the Social Appearance Anxiety Scale and spiritual development, interpersonal relationships.
Keywords: Nutritional status; healthy lifestyle behaviors; social appearance anxiety; ORTO-15; ORTHOREXIA NERVOSA; ASSOCIATION; SYMPTOMS; STUDENTS; RISK